Chlorine induced high-temperature corrosion mechanisms in HVOF and HVAF sprayed Cr3C2-based hardmetal coatings. (November 2019) - Fantozzi, Davide; Matikainen, Ville; Uusitalo, Mikko; Koivuluoto, Heli; Vuoristo, Petri
Highlights: High temperature corrosion properties of HVOF and HVAF Cr3 C2 -based coatings. Synergistic use of TGA and furnace corrosion tests. A corrosion mechanism for chloritizing-oxidizing condition was proposed. Temperature ranges were identified for the onset of chlorine corrosion. Fine secondary carbide precipitates were highly detrimental in the test conditions. Abstract: A novel method that combines thermal analysis and traditional furnace corrosion tests was used to study the corrosion behaviour of thermally sprayed Cr3 C2 -based hardmetal coatings at 450 °C and 550 °C under a KCl deposit. This method enabled the identification of the onset temperature of chlorine-induced oxidation to be within 450–500 °C. Two corrosion mechanisms were suggested for these temperatures. At 450 °C, the corrosion rate was slow and mainly controlled by the formation of K2 CrO4 . Exposure at 550 °C caused the formation of fine interconnected secondary-carbide precipitates in the metal matrix. Their fast corrosion was identified as the major cause of degradation.